2003
DOI: 10.1002/mrc.1188
|View full text |Cite
|
Sign up to set email alerts
|

DFT/FPT studies of the structural dependencies of long‐range 1H,1H coupling over four bonds 4J(H,H′) in propanic and allylic systems

Abstract: A study is presented of the structural dependencies for scalar J-coupling across four bonds in propanic and allylic systems. Density functional theory (DFT) and finite perturbation theory (FPT) were used to obtain the Fermi contact (FC) contributions to 1 H, 1 H coupling. Interproton couplings 4 J(H,H ) in propane were obtained as functions of the dihedral angles j 1 and j 3 , which are measured about the C(1) -C(2) and C(2) -C(3) bonds, respectively, and on the C(1) -C(2) -C(3) internal angle q 2 . A four-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…This is because of the acute bond angle of 94.7° for C1-C4-C3 and the large dihedral angles of 145.2° for H1eq-C1-C4-C3 and -145.2° for C1-C4-C3-H3eq; the other values are too small to observe using a 400 MHz NMR instrument. 18 This observation is in quite contrast of 1 H NMR of 3, which showed only one averaged singlet in toluene-d 8 even at -70 °C. It is because the racemization barrier (inversion barrier of the thietane ring) was calculated to be 1.1 kcal/mol at the BMK/6-311+G(d,p)//B3LYP/6-31G(d) level.…”
Section: 1617mentioning
confidence: 68%
“…This is because of the acute bond angle of 94.7° for C1-C4-C3 and the large dihedral angles of 145.2° for H1eq-C1-C4-C3 and -145.2° for C1-C4-C3-H3eq; the other values are too small to observe using a 400 MHz NMR instrument. 18 This observation is in quite contrast of 1 H NMR of 3, which showed only one averaged singlet in toluene-d 8 even at -70 °C. It is because the racemization barrier (inversion barrier of the thietane ring) was calculated to be 1.1 kcal/mol at the BMK/6-311+G(d,p)//B3LYP/6-31G(d) level.…”
Section: 1617mentioning
confidence: 68%
“…These interactions are thought to be responsible for the differences between the exo-exo and endo-endo vicinal coupling constants in bicycloalkanes. 67 Also, in a previous study of long range H-H coupling, 33 it was concluded that trigonometric equations applicable to propane coupling could not account for many features of 4 J(H,H) in the cyclic compounds.…”
Section: Bicyclic Compoundsmentioning
confidence: 96%
“…The solid line is a plot of the linear regression result from Eqn (34). The squares depict the aug-cc-pV(D)Z-J results from Table 2 scaled according to Eqn (33). The scaling is used only to show that the computed results include all of the subtle features of coupling in the bicyclic molecules.…”
Section: Bicyclic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations